Exosomes in early lung cancer diagnostics: the current state of progress made and prospects - Liu, Xiaotian; Xu, Xianlin; Wang, Qian (Frontiers in Cell and Developmental Biology, 2026)
The high mortality rate of lung cancer primarily results from its late-stage diagnosis, at which point metastasis has usually occurred and therapeutic options are limited, leading to an overall 5-year survival rate below 20% in most countries. The current screening method, low-dose computed tomography (LDCT), faces challenges such as high false-positive rates, which can result in overdiagnosis and unnecessary surgeries, as well as the risk of cancer due to repeated exposure to ionizing radiation. Although tumor tissue detection remains the gold standard for cancer diagnosis, it is limited by invasive sampling procedures that may cause patient trauma, as well as by tumor heterogeneity and inconsistent tissue quality, which can compromise diagnostic accuracy. Due to these challenges among others, researchers have been exploring better diagnostic methods that are not only sensitive and specific but also non-invasive, utilizing easily available samples with good reproducibility. In recent years, studies have revealed that humoral-derived materials, such as exosomal RNAs and proteins are considered the most promising biomarkers for the early diagnosis of lung cancer in body fluids owing to their stability, accessibility, and specificity. This study reviews current research on the exploration of exosomes as early diagnostic markers for lung cancer. Both established methods and emerging technologies, such as surface-enhanced Raman spectroscopy (SERS), lateral flow immunoassays (LFIA), microfluidics, and electric field-induced release and measurement (EFIRM), as well as commercial products, are discussed.